Crossover of Flow from Music Teachers to Students: The Role of Teachers’ Work Orientations - Rijavec, Majda; Ljubin Golub, Tajana; Ivanković, Melita (Studia Psychologica, 2024)
The present study examined the role of work orientations in music teachers’ experiences of flow in teaching, and the crossover of flow from teachers to their students. The sample comprised 135 music teachers and 484 students from 7 different music schools in Croatia. Based on the theory of work orientation, flow theory, and emotional contagion theory, it was hypothesized that seeing one’s job just as the source of material benefits leads to less frequent flow in teaching, while orientation to work as a calling leads to more frequent flow in teaching, which in turn crosses over to students. Questionnaires for measuring work orientations and flow in teachers and students were applied. Data were analyzed using structural equation modeling and the model demonstrated an excellent fit. Practical implications of these results point to the importance of cultivating the calling orientation of teachers in order to facilitate their experience of flow in teaching and consequently the crossover of flow to students.